The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1101/2023.11.20.567915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Septins throughout phylogeny are predicted to have a transmembrane domain, which inCaenorhabditis elegansis functionally important

Jenna A. Perry,
Michael E. Werner,
Bryan W. Heck
et al.

Abstract: SUMMARYSeptins, a conserved family of filament-forming proteins, contribute to eukaryotic cell division, polarity, and membrane trafficking. Septins are thought to act in these processes by scaffolding other proteins to the plasma membrane. The mechanisms by which septins associate with the plasma membrane are not well understood but can involve two polybasic domains and/or an amphipathic helix. We discovered that the genomes of organisms throughout phylogeny, but not most commonly used model organisms, encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This distribution of TM domains in our dataset seems to suggest that they emerged early in the non-opisthokont branch after its split with opisthokonts and were subsequently lost in many species in Group 6B and 8. [See, however, Discussion for another possibility given a recent report by (Perry et al, 2023). ] It is interesting to note that there is little overlap between the distributions of CC and TM domains in Group 6 septins (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution of TM domains in our dataset seems to suggest that they emerged early in the non-opisthokont branch after its split with opisthokonts and were subsequently lost in many species in Group 6B and 8. [See, however, Discussion for another possibility given a recent report by (Perry et al, 2023). ] It is interesting to note that there is little overlap between the distributions of CC and TM domains in Group 6 septins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We initially interpreted this as evidence that the TM domain emerged after the opisthokont/non-opisthokont split and was subsequently lost in some lineages. However, a recent study by Perry et al (2023) reported the presence of TM domains in a transcript isoform of C. elegans UNC-61 (Group 1) as well as many other opisthokont proteins currently annotated as septins on the Uniprot database (but were not included in our list of 254 septins). Interestingly, many of these TM domains are found in the NTE, as seen in C. anguillulae A0A1Y2I4M7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This distribution of TM domains in our dataset seems to suggest that they emerged early in the non-opisthokont branch after its split with opisthokonts and were subsequently lost in many species in Group 6B and 8. [See, however, Discussion for another possibility given a recent report by ( Perry et al, 2023 ).] It is interesting to note that there is little overlap between the distributions of CC and TM domains in Group 6 septins ( Figure 7D ), perhaps suggesting that the evolution of septin-septin interactions through CC domains necessitated a concomitant loss of TM that would otherwise restrict the accessibility of CTE.…”
Section: Resultsmentioning
confidence: 99%
“…We initially interpreted this as evidence that the TM domain emerged after the opisthokont/non-opisthokont split and was subsequently lost in some lineages. However, a recent study by Perry et al (2023) reported the presence of TM domains in a transcript isoform of C. elegans UNC-61 (Group 1) as well as many other opisthokont proteins currently annotated as septins on the Uniprot database (but were not included in our list of 254 septins). Interestingly, many of these TM domains are found in the NTE, as seen in C. anguillulae A0A1Y2I4M7 ( Figure 7E ).…”
Section: Discussionmentioning
confidence: 99%
“…This distribution of TM domains in our dataset seems to suggest that they emerged early in the non-opisthokont branch after its split with opisthokonts and were subsequently lost in many species in Group 6B and 8. [See, however, Discussion for another possibility given a recent report by (Perry et al, 2023).] It is interesting to note that there is little overlap between the distributions of CC and TM domains in Group 6 septins (Figure 7D), perhaps suggesting that the evolution of septinseptin interactions through CC domains necessitated a concomitant loss of TM that would otherwise restrict the accessibility of CTE.…”
Section: Selective Distribution Of Coiled-coil and Transmembrane Doma...mentioning
confidence: 91%